Profile of Pregnant Women with Hypertension: A Cross Sectional Study in Jambi City - Rina Nofri Enis; Essy Octavia; Herlambang, Herlambang; Kusdiyah, Erny; Hulwa Atika Adilita (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2024)
Background: Hypertension in pregnancy is one of the complications that cause maternal death in Indonesia. The incidence of hypertension during pregnancy is influenced by a variety of factors.Objective: This study aims to determine maternal characteristics with hypertension in pregnancy at the Raden Mattaher Jambi General Hospital.Methods: This is a descriptive research using secondary data sources. This study population included all pregnant and delivering mothers who were diagnosed with hypertension in pregnancy between 2019 and 2022 with a total of 169 samples.Results: The results of this study are the average age of mothers is not at risk (63.3%), housewives (83.4%), senior high school education status (58.6%), diagnosed with preeclampsia (71.6%), with severe preeclampsia category (93.4%), gestational age aterm (59.2%), multiparous (59.8%), grade 2 hypertension (68%), positive proteinuria status (63.9%), high ureum levels (60.9%), normal creatinine level (79.3%), decreased hemoglobin level (53.3%), normal platelet count (84%), leukocytosis (78.7%), normal erythrocyte level (61.5%), normal hematocrit value (53.8%), normal blood sugar level (86.4%), obesity class 1 (43.2%), no history of hypertension (59.2%), no history of preeclampsia (72.2%), regular antenatal visits (65.1%), and sectio cesarea method (88.2%).Conclusion: Maternal characteristics were identified as age not at risk, housewife, senior high school education, diagnosed with preeclampsia, aterm, multiparous, grade 2 hypertension, positive proteinuria status, increased ureum level, normal creatinine level, decreased hemoglobin level, normal platelet count, leukocytosis, normal erythrocyte level, normal hematocrit value, normal blood sugar level, obesity type 1, no history of hypertension, no history of preeclampsia, history of regular antenatal visits, and sectio cesarea method.Keywords: Hypertension in Pregnancy, Preeclampsia, Jambi